(untitled) (Journal of Informatics Education and Research, 2025)
It is a research study involving the implementation of Artificial intelligence (AI) in the Human Resource Management (HRM) to organize the real time wage tariff and optimize the budgets. The analysis of the secondary data sources (industry report, scholarly publications, and market research) allows the research to confirm that the AI technologies, and specifically machine learning, natural language processing, and predictive analytics transform the conventional HR functions radically. Such findings imply that AI-based systems can assist organisations to create dynamic impacts in compensation, dynamically react to a given change in the market and attain a new level of budgetary accuracy and business efficiencies. The paper has determined the most prevalent applications of technology, measures the implications of the applications by the available statistics and also covers the major issues of implementation such as data governance, bias in the algorithms and skills gaps.